MURAJA'AH LEARNING METHOD ON HOME TAHFIZH QUR'AN AN-NUUR - Feni Mercellina; Muhammad Adil; Karoma Karoma (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
This study is aimed to analysis how the implementation of muraja'ah method to keep the Holy Qur’an memorization and the factors that influence its processes of implementing Qur’an learning method at Tahfizh Qur’an An-Nuur Sekayu.The type of this study is a field research. This study is presented in a descriptive qualitative method with the aim to describe a process occurs in the field setting. The approach applied in this study is a qualitative approach. Data collection techniques used are including: interview, observation and documentation methods. To analyze the data obtained from the results of the study, the writer used Miles and Huberman's interactive model data analysis techniques. Whereas to obtain data validity is determined by four criteria, namely the level of credibility, transferability, dependability, and confirmability. The results of the study are (1). The implementation of the Holy Qur’an learning at Tahfizh Qur’an An-Nuur Sekayu emphasizes the students to always apply muraja'ah method to keep the memorization of the Holy Quran. (2). Some factors that influence the implementation process of Tahfizh Qur’an learning are including: internal factors (the spirit within the students, health of students, intelligence, interests and motivation) and external factors (support from parents, teachers and friends).